Strategi Kepala Sekolah dalam Memaksimalkan Supervisi melalui Pendidikan berbasis Budaya - Nur Qorimah, Esti; Laksono, Wisnu Cahyo (LPPM Press, 2023)
The purpose of this study is to describe culture-based education, implementation strategies for culture-based education, components of culture-based learning, constraints and solutions in the implementation of culture-based education. The method used in research is literature review contains a brief overview of a research topic and is organized chronologically and thematically. The results of this study are: 1) Culture-based education to instill cultural values in a child; 2) Strategies in culture-based education are carried out through culture-based learning, integration of learning themes, learning support activities, school culture; 3) the culture-based learning component consists of substance (material) and competence or fields of science, meaningfulness and learning process, assessment of learning outcomes, and the role of culture; 4) Obstacles in implementing it, namely lack of teaching media, teachers find it difficult to find local culture in the environment around the school, teachers have difficulty in integrating culture with the material to be taught, teachers have not been creative to develop learning media or teaching materials.